1997
DOI: 10.1103/physreva.55.3639
|View full text |Cite
|
Sign up to set email alerts
|

Stability of solutions of the nonlinear Schrödinger equation for trapped Bose-condensed atoms with negative scattering lengths

Abstract: We analyze the time evolution of solutions of nonlinear Schrödinger equations that describe a condensate composed of atoms with negative scattering lengths in a harmonic potential trap. It is theoretically demonstrated that if an initial condensate has negative energies due to negative scattering lengths, then the solutions diverge in a finite time that is determined by the condensate's energy, its initial phase, and the trap parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…The latter value of N c,new agrees well with the one in the experiment, which is about 10 3[13]. It is also consistent with the theoretical ones obtained by different approaches, which are (1 ∼ 3) × 10 3 [31]-[40],[45]-[51].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The latter value of N c,new agrees well with the one in the experiment, which is about 10 3[13]. It is also consistent with the theoretical ones obtained by different approaches, which are (1 ∼ 3) × 10 3 [31]-[40],[45]-[51].…”
supporting
confidence: 90%
“…This problem has been discussed also in Refs. [79,45]. For g = −1, the energy (4.1.4) with the harmonic potential (4.1.2) is written as…”
Section: ) H ≤ 0 Casementioning
confidence: 99%
“…This is agreement with Pitaevskii's analysis of the system [24], where it is shown that an attractive interaction leads to collapse of the gas for energies more than ω below the ideal gas ground state energy. Similar conclusions are drawn in [25]. The results of the many-body calculation are compared to the mean field approximation (Gross-Pitaevskii), which is approached as the particle number increases.…”
Section: A Ground State Energymentioning
confidence: 53%
“…By combining Eqs. (16) and (17) we get the following second-order differential equation for the evolution of the widtḧ…”
Section: Variational Approach and Governing Equationsmentioning
confidence: 99%
“…Due to the diluteness of BEC, most theoretical works on collective excitations are mainly focused on considering the two-body interaction by means of the Gross-Pitaevskii equation (GPE) [6,7,8,9]. A long side with the experimental progress with BECs in atomic waveguides and on the surface of atomic chips, which involve a strong compression of the traps, a significant increase of the density of BECs can be achieved; thus, three-body interaction may also play an important role in the process of collective excitations [10,11,12,13], and stability of trapped BEC [14,15,16]. Specially, it is reported in Ref.…”
Section: Introductionmentioning
confidence: 99%